The Words and phrases of Urdu Language in English Dictionaries (18th to 20th Century) - Masroor Siddiqui, Arooba; Razzaq, Shazia (sourcecoder, 2022)
British entered Subcontinent in 15th century. Soon they took a strong grip on all central areas and regions of India, politically, economically and socially. In 18th century they ruled the whole Hindustan. During this period, most of the words of English language entered in Urdu Language and Literature and vice versa. After that those words and phrases became the part of their dictionaries with the same meanings and references with the similar sounds even. This article is about those famous words,(phrases) which are similar in Urdu and English dictionaries and now have become the part of both languages.